2011
DOI: 10.11004/kosacs.2011.2.1.030
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study for the Compression Strength of Hybrid CFFT Pile

Abstract: In this paper, we persent the results of on experimental investigations pertaining to the structural behavior of new type of concrete filled fiber reinforced plastic circular tubes (i.e., hybrid CFFT, HCFFT) which are suggested in order to mitigate the problems associated with the concrete filled steel-concrete composite tube (CFT) and the concrete filled fiber reinforced plastic tube (CFFT). It is found that when the HCFFT is used in the construction of pile foundation the HCFFT pile can transfer axial as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…FEA was performed by reflecting the size of the experimental member, standard design strength of concrete, and FRP thickness. The mechanical properties of the hybrid-CFFT obtained from a previous study [26] were applied, which are shown in Table 10. For the boundary conditions, all the lower surfaces of the analysis model were fixed.…”
Section: Finite Element Analysismentioning
confidence: 99%
“…FEA was performed by reflecting the size of the experimental member, standard design strength of concrete, and FRP thickness. The mechanical properties of the hybrid-CFFT obtained from a previous study [26] were applied, which are shown in Table 10. For the boundary conditions, all the lower surfaces of the analysis model were fixed.…”
Section: Finite Element Analysismentioning
confidence: 99%
“…The research results of Choi et al [ 10 ] confirmed that the compressive strength of HCFFT is higher than that of CFFT because FFRP reinforced PFRP. The research results of Lee et al [ 11 ] confirmed that it is economical to design an FFRP with a thickness of 4.2 mm or less, and that the increase in strength decreases when it exceeds 4.2 mm.…”
Section: Results Of the Flexural Strength Test Of Hcfft Specimens And...mentioning
confidence: 96%
“…The design of the cross-section of the HCFFT specimens was determined based on the results of compressive strength testing of CFFT obtained by Choi et al and Kang and Kim [ 10 , 12 ]. The geometry of the cross-section of HCFFT is illustrated in Figure 9 .…”
Section: Flexural Strength Test Of Hcfft Specimensmentioning
confidence: 99%
See 2 more Smart Citations